The right of children of incarcerated persons to family life: Towards a more child-centred approach - Wambui, Anita Eunice (Strathmore University, 2021)
All children are vulnerable members of society and require the protection of the family and the State. This vulnerability is heightened when children are separated from their parents, in which case, they should be allowed to maintain contact with them unless it is contrary to their best interest. This applies even when the separation is state-sanctioned such as detention, imprisonment or any other legal deprivation of liberty. The State, in such instances, has the twin responsibilities of non-interference with the family life of these children, and the mandate to adopt measures to ensure that this right is protected. This paper focuses on the dissonances in the laws governing contact and visitation, from a child’s rights perspective and a prisoner’s rights perspective, and how these dissonances translate into the reality of this children. It aims to shed light on the negative consequences of only adopting visitation laws and policies from a prisoner’s rights perspective. This is because they frame what should ideally be a child’s right as a prisoner’s privilege, which can be taken away at the will of the prison officials. The research methodology applied in this paper is desktop research and zoom interviews to obtain empirical data and to inform the literature review. The paper analyses child laws relevant to children of imprisoned parents against the four guiding principles of the CRC and juxtaposes these rights with the provisions on prisoner’s rights. It finds that the problematic framing of contact and visitation as a ‘privilege’ often violates the child’s right to maintain a family life with his or her imprisoned parents. It briefly highlights the situation in the Council of Europe, greatly attributing the good practices to the existence of a child-centred policy. It draws on this policy and practice to make recommendations to improve the situation in Kenya. Its main recommendation is that the child should be the focus of any policy likely to affect him or her
Submitted in partial fulfilment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School